Ocena instrumentów stymulowania lokalnego rozwoju gospodarczego - Kulas, Iwona (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The objective of the article is the research focused on evaluation of providing local economic policy with special attendance to the set of using instruments and to the effects that were achieved.The main goal of the research was achieving the local governments' opinion on effectiveness of existing development stimulators. There was also a trial of finding the correlation between amount and type used tools and final effect that was assumed in research as local economic development dynamic of researched communes.For the sake of complexity of researched phenomenon, not all results let for clear-out interpretation. The most important conclusion is that higher dynamic of development was characteristic for the communes preferring long-term policy with using new methods and tools typical for new public management. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 278-284